1994
DOI: 10.1007/bf00004300
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between biochemical constituents of fish semen and fertility: the effect of short-term storage

Abstract: Spermatozoa and seminal plasma obtained from rainbow trout and whitefish were analyzed in respect to their aspartate aminotransferase (AspAT) and alkaline phosphatase activities. In particular, the experiments characterized AspAT optimum pH, optimization of assay conditions and action of coenzyme, pyridoxal 5-phosphate (vitamin B6). The effect of short-term semen storage at 0°C on biochemical indicators and fertilization rate was examined in both species. The concentrations of reduced and oxidized ascorbic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(66 citation statements)
references
References 38 publications
5
60
1
Order By: Relevance
“…Our results confirmed the data of Munkittrick and Moccia (29) and Ciereszko and Dabrowski (14) who found a correlation between motility rate and fertilization capacity for the trout sperm using subjective estimation methods for motility determination. Magyary et al (26) concluded a strong, positive correlation of frozen-thawed carp spermatozoa motility and fertility at 1-1.5x10 5 :1 spermatozoa/egg ratio.…”
Section: Discussionsupporting
confidence: 92%
“…Our results confirmed the data of Munkittrick and Moccia (29) and Ciereszko and Dabrowski (14) who found a correlation between motility rate and fertilization capacity for the trout sperm using subjective estimation methods for motility determination. Magyary et al (26) concluded a strong, positive correlation of frozen-thawed carp spermatozoa motility and fertility at 1-1.5x10 5 :1 spermatozoa/egg ratio.…”
Section: Discussionsupporting
confidence: 92%
“…All sperm used in this study had an initial motility rate of at least 80% (see Fig. 1 (Billard, 1981;Billard and Legendre, 1982;Hara et al, 1982;Stoss and Refstie, 1983;Ciereszko and Dabrowski, 1994;Dilauro et al, 1994;Bencic et al, 2000;Jenkins-Keeran et al, 2001), as compared to the results reported here for Neotropical fishes. The high percentages of P. marggravii eggs that were fertilised with 8 h stored sperm, comparable to those obtained with fresh sperm under routine hatchery conditions (Sato et al, 1996), confirmed the applicability of the cooling preservation technique described herein.…”
Section: Discussionsupporting
confidence: 61%
“…Cold storage is a simple technique that allows sperm to be available at various time intervals, for the fertilisation of eggs produced by hormone-induced females, which ensures greater productivity in the reproductive process. By facilitating the use of sperm from a larger number of males per female, it can help improve the genetic quality of the resulting offspring, in addition to allowing the characteristics of the sperm to be studied (Ciereszko and Dabrowski, 1994). An additional advantage is the ease of transport in appropriate containers (Henderson and Dewar, 1959).…”
Section: Introductionmentioning
confidence: 99%
“…Our results confirmed the data of Munkittrick and Moccia (1987) and of Ciereszko and Dabrowski (1994) who found a correlation between motility rate and fertilization capacity for the rainbow trout sperm using subjective estimation methods for motility determination. Magyary et al (1996) concluded a strong, positive correlation (r=0.85) of frozen/thawed carp spermatozoa motility and fertility at 1x10 5 -1.5x10 5 :1 spermatozoa/egg ratio.…”
Section: Resultssupporting
confidence: 91%